Revival and Its Legacy: Acase Study of the East African Revival Movement in Bugangari Archdeaconry North Kigezi Diocese - Lewin Nimusiima (Uganda Christian University, 2025)
The East Africa Revival Movement (EARM) has significantly influenced many Protestant churches in Eastern Africa for years. It has renewed their spirit and challenged individuals to seek a deeper experience of salvation in Christ, along with a stronger commitment to Christian discipleship and evangelism. Despite the presence of other revivals in the region, the Revival Movement has played a vital role in the growth of the church in East Africa. This report focuses on Bugangari Archdeaconry within the North Kigezi Diocese. The parish faces significant controversies among Christians regarding the values, beliefs, and practices of EARM. This study aimed to investigate how EARM teachings, beliefs, and practices affect evangelism and the spiritual lives of Christians in Bugangari Archdeaconry. Specifically, the study sought to accomplish the following objectives; To explore how the East African Revival Movement influenced the spiritual life of Christians in Bugangari Parish. To identify the challenges posed by the East African Revival Movement in Bugangari Parish. To suggest strategies the church can implement to address these challenges related to the East African Revival Movement in Bugangari Parish. The area of study consists of five churches within the parish, namely Bugangari, Rwanyanja, Burembo, Kitunguru, and Nyakariro. The report is organized into six chapters: introduction, literature review, methodology, data presentation, theological reflection and discussions, summary, and conclusion. The research findings indicate that EARM has affected the church’s efforts to nurture Christians both socially and spiritually. However, those associated with EARM, known as Barokole, have different spiritual practices in their beliefs. The researcher recommended strategies to enhance the beliefs and practices of EARM among the Christians of Bugangari Archdeaconry. The findings also suggest that Christians are familiar with Barokole, or born-again Christians, and they have observed the movement’s effects on their spiritual lives through their feedback. Additionally, the researcher proposed further study on EARM beliefs and practices and encouraged the church to adopt strategies that address the spiritual challenges facing their congregation.
Undergraduate Research